Great expectations? Evidence from Colombia's exchange rate survey - Juan Jose Echavarria; Mauricio Villamizar-Villegas (Latin American Economic Review, 2016)
In this paper, we use the largest exchange rate survey in Colombia to test for the rational expectations hypothesis, the presence of a time-varying risk premium and the accuracy of exchange rate forecasts. Our findings indicate that episodes of exchange rate appreciation preceded expectations of further appreciation in the short run, but were marked by depreciations in the long run. This reversal largely explains the stabilizing pattern of expectations. Additionally, we find that the forward discount differed from future exchange rate changes due to the rejection of the unbiasedness condition and to the presence of a time-varying risk premium. Finally, we find that only short run expectations were able to outperform a random walk process as well as models of extrapolative, adaptive, and regressive expectations. Long-run expectations, on the other hand, behaved poorly in terms of forecasting accuracy.
Keywords: C23; C53; C83; F31; F37; 330; Exchange rate expectations; Risk premium; Forecasting accuracy; Random walk; Forward discount; Rational expectations hypothesis